(untitled) (Third Sector Social Economic Review, 2015)
The study was conducted to determine organization related problems of producers were the members of rural development cooperatives and to preset solution proposals in Iğdır province. The data surveyed from rural development cooperative member producers determined in Iğdır and territories by simple random sampling method are used in this study. It is determined that agricultural cooperative members do not have enough information regarding establishing organizations, do not join the activities, and have problems with financing, management, trust and regulations. The members should be educated about the cooperatives and their importance. They should also be encouraged to join the activities effectively, provided enough flexibility in financing. Moreover, a trusting environment should be established in cooperatives and the regulations must be revised based on the current needs of producers.